Fetus in fetu in an adult woman. Issue 8 (12th August 2019) - Kumar, Anil; Paswan, Shiv Shankar; Kumar, Bindey; Kumar, Prem
Abstract : Fetus in fetu (FIF) is an extremely rare condition in which malformed fetus is found most commonly in the retroperitoneum of living twin. It occurs in about 1 in 500 000 live births and less than 200 cases have been reported in medical literature. We report FIF in a 17-year-old woman unlike other cases which were usually detected in early age and in male gender. This is the eighth case of adult FIF and the first case of FIF in adult woman worldwide. Preoperative diagnosis of FIF on CT was made and planned for exploratory laparotomy. The excised malformed fetus in a sac was proven as FIF on the basis of histopathological examination. In view to avoid such late presentation, early detection of FIF with radiological imaging in clinically suspected case is recommended. Surgical excision is the ideal treatment even teratoma is the differential diagnosis.